2006
DOI: 10.1111/j.1440-1754.2006.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of the management of severe malnutrition: 3. Complications

Abstract: The high case-fatality of severe malnutrition is due to infections, dehydration, electrolyte disturbances and heart failure. We focus on the evidence about managing these complications of severe malnutrition. Signs of circulatory collapse in severely malnourished children should be treated with intravenous or bone marrow infusion of Ringer's lactate with additional dextrose and potassium at a rate 20-40 mL/kg fast with close monitoring of vital signs. Recommendations for slow or restricted fluids in the face o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 103 publications
2
24
0
Order By: Relevance
“…Similar findings were reported from Kenya where diarrhea was a common complication (49%) resulting in higher mortality in children hospitalized with severe acute malnutrition [22] and children with severe malnutrition are more prone to infections than others due to the immunosuppressive effect of malnutrition and the loss of the protective mucosal barrier in the gastrointestinal tract [23]. Moreover, studies have shown that severely malnourished children are more prone to gut barrier dysfunction [24], Escherichia coli bacteraemia [25] and higher mortality from invasive bacterial infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported from Kenya where diarrhea was a common complication (49%) resulting in higher mortality in children hospitalized with severe acute malnutrition [22] and children with severe malnutrition are more prone to infections than others due to the immunosuppressive effect of malnutrition and the loss of the protective mucosal barrier in the gastrointestinal tract [23]. Moreover, studies have shown that severely malnourished children are more prone to gut barrier dysfunction [24], Escherichia coli bacteraemia [25] and higher mortality from invasive bacterial infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that malnutrition affects over 150 million children worldwide and is associated with 45% of all child deaths 1. Malnutrition-related mortality is primarily associated with infection or dehydration, but often there is no other identifiable cause of death 2 3. Some researchers have proposed that cardiac dysfunction may be associated with these unexplained deaths either directly or through decompensation after aggressive fluid resuscitation 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that with strict adherence to these guidelines the mortality should be < 5% (13,14) . Whilst high case-fatality rates are often attributed to faulty case management, the evidence for this assertion is poor and other workers have suggested that outcome is largely dependent on other antecedent factors, including the frequency of additional life-threatening complications (4,(15)(16)(17)(18) . The current guidelines have largely been based on expert or consensus opinion.…”
mentioning
confidence: 99%